Distinct functions of elongation factor G in ribosome recycling and translocation - Savelsbergh, Andreas (Cold Spring Harbor Laboratory Press, 2009)
Elongation factor G (EF-G) promotes the translocation step in bacterial protein synthesis and, together with ribosome recycling factor (RRF), the disassembly of the post-termination ribosome. Unlike translocation, ribosome disassembly strictly requires GTP hydrolysis by EF-G. Here we report that ribosome disassembly is strongly inhibited by vanadate, an analog of inorganic phosphate (Pi), indicating that Pi release is required for ribosome disassembly. In contrast, the function of EF-G in single-round translocation is not affected by vanadate, while the turnover reaction is strongly inhibited. We also show that the antibiotic fusidic acid blocks ribosome disassembly by EF-G/RRF at a 1000-fold lower concentration than required for the inhibition of EF-G turnover in vitro and close to the effective inhibitory concentration in vivo, suggesting that the antimicrobial activity of fusidic acid is primarily due to the direct inhibition of ribosome recycling. Our results indicate that conformational coupling between EF-G and the ribosome is principally different in translocation and ribosome disassembly. Pi release is not required for the mechanochemical function of EF-G in translocation, whereas the interactions between RRF and EF-G introduce tight coupling between the conformational change of EF-G induced by Pi release and ribosome disassembly.